Homocysteine and cognitive function in Parkinson's disease. (November 2017) - Licking, Nicole; Murchison, Charles; Cholerton, Brenna; Zabetian, Cyrus P.; Hu, Shu-Ching; Montine, Thomas J.; Peterson-Hiller, Amie L.; Chung, Kathryn A.; Edwards, Karen; Leverenz, James B.; Quinn, Joseph F.
Abstract: Introduction: Increased plasma homocysteine (HC) is a risk factor for dementia in the general population. Levodopa therapy causes increased plasma HC, but it remains unclear whether elevated plasma HC is associated with cognitive impairment in Parkinson's disease (PD). Methods: The study population includes all participants in the Pacific Northwest Udall Center (PANUC) Clinical cohort at the time of the study, consisting of 294 individuals with PD who had a standardized neuropsychological assessment and plasma collection for HC measurement. We tested the hypothesis that elevated plasma HC is inversely related to cognitive function in patients with PD. Results: As expected, plasma HC was positively associated with age, disease duration, disease severity, and levodopa usage, while cognitive function was associated with age, education, gender, and APOE genotype, so subsequent analyses controlled for these covariates. When plasma HC was dichotomized as normal (<14 μmol/L) or elevated (≥14 μmol/L), subjects with hyper-homocysteinemia had lower scores on Digit Symbol (p = 0.031), Hopkins Verbal Learning Task (HVLT) Delayed Recall (p = 0.004), and semantic verbal fluency (p = 0.049). When examined as a continuous variable, plasma HC was inversely associated with HVLT Delayed Recall (p = 0.009)) and semantic verbal fluency (p = 0.004), but was not significantly related to Digit symbol, Trail-making test, Judgment of Line Orientation, phonemic verbal fluency, MMSE, or MOCA. When analysis was restricted to non-demented subjects (n = 231), the findings were unchanged. Conclusions: We conclude that plasma HC is significantly associated with some aspects of cognitive function in PD, and may represent a treatable risk factor for cognitive decline in PD. Highlights: Elevated plasma homocysteine was associated with levodopa use and with age. Elevated plasma homocysteine was associated with poor cognitive performance in PD. Homocysteine is inversely correlated with tests of memory and verbal fluency in PD.